Learning in networks: An experimental study using stationary concepts - Siegfried Berninghaus; Thomas Neumann; Bodo Vogt (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
Our study analyzes theories of learning for strategic interactions in networks. Participants played two of the 2 x 2 games used by Selten and Chmura (2008) and in the comment by Brunner, Camerer and Goeree (2009). Every participant played against four neighbors and could choose a different strategy against each of them. The games were played in two network structures: a attice and a circle. We compare our results with the predictions of different theories (Nash equilibrium, quantal response equilibrium, action-sampling equilibrium, payoff-sampling equilibrium, and impulse balance equilibrium) and the experimental results of Selten and Chmura (2008). One result is that the majority of players choose the same strategy against each neighbor. As another result we observe an order of predictive success for the stationary concepts that is different from the order shown by Selten and Chmura. This result supports our view that learning in networks is different from learning in random matching.
Keywords: C70; C73; C91; D83; D85; 330; experimental economics; networks; learning; Dynamisches Spiel; Soziales Netzwerk; Lernprozess; Test